Unveiling income disparities in rural E-commerce landscape: Evidence from China - Jiaxin Du; Chao Zhong; Qiaoling Shi; Zhonghua Zhang (Sustainable Futures)
China's rural e-commerce (EC) has grown significantly, recognized as a crucial tool for rural development. However, income effects of rural e-commerce vary among different groups of farmers due to their distinct roles and benefits, raising the possibility of a ''mean trap'' in previous studies whereby regional farmer income averages have been used to indicate rural e-commerce benefits. Using Meta-Regression Analysis (MRA), the study found that the income effect is more common in EC-active minority groups with higher access and participation levels. Enhanced incomes mainly occurred among marketing-oriented farmers, with limited impact at the village level and predominantly at the county level.